AB149. Is two-layer suture necessary in laparoscopic partial nephrectomy? - Chen, Fan (Transl Androl Urol, 2016)
OBJECTIVE: We intend to discuss the applications of various suture techniques and the necessity of two-layer suture in the wound suturing in the laparoscopic partial nephrectomy. METHODS: A literature search and review in the PubMed and Wanfang databases was conducted with the key words of ‘two-layer suture’ and ‘laparoscopic partial nephrectomy’. RESULTS: It is believed currently that there exist many different methods of sutures and compared to single-layer suture, two-layer suture is a relatively stable and safe kind of suture, which can shorten the warm ischemic time and reduce the incidence of complications. However, it also can increase the difficulty in operating for surgeons and impair the functional renal preservation. CONCLUSIONS: So it is supposed to weigh the advantages and disadvantages of two-layer suture and single-layer suture flexibly and make the proper clinical choice.